2014
DOI: 10.1007/s12031-013-0214-2
|View full text |Cite
|
Sign up to set email alerts
|

Higher Circulating Levels of Chemokine CCL20 in Patients with Multiple Sclerosis: Evaluation of the Influences of Chemokine Gene Polymorphism, Gender, Treatment and Disease Pattern

Abstract: Chemokines play an important role in the autoimmune diseases. The aim of this study was to investigate the levels of CCL20 and a polymorphism [-786C > T (rs6749704)] in the chemokine gene in patients with multiple sclerosis (MS). The blood samples were collected from 135 MS patients and 135 healthy subjects as a control group. The patients have relapsing-remitting (RRMS; n = 65), primary progressive (PPMS; n = 47), secondary progressive (SPMS; n = 35) or progressive relapsing (PRMS; n = 14) patterns. The serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
2
22
1
Order By: Relevance
“…The accompanying polymorphism of the gene in MS patients in Egypt shows an increased risk of MS rather than an individual locus [29]. Another study from Iran showed that the rs6749704 polymorphism is associated with the SPMS model [45].…”
Section: Ccl20/ccr6mentioning
confidence: 99%
“…The accompanying polymorphism of the gene in MS patients in Egypt shows an increased risk of MS rather than an individual locus [29]. Another study from Iran showed that the rs6749704 polymorphism is associated with the SPMS model [45].…”
Section: Ccl20/ccr6mentioning
confidence: 99%
“…The role of Th2 cells, which secrete high levels of IL-4, IL-5, and IL-13, remains controversial (Raphael et al 2015). We have previously observed the elevated concentrations of a Th17-related chemokine (CCL20), diminished levels of a Th2/Treg-related chemokine (CCL22), and unchanged levels of a Treg-related cytokine in patients with MS (Jafarzadeh et al 2014a;Jafarzadeh et al 2014b;Jafarzadeh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since its initial cloning, CCL20 has been implicated in a diverse set of inflammatory conditions, including rheumatoid arthritis [31], multiple sclerosis [32] and islet viral infection [33]. Indeed, CCL20 is able to chemoattract both adaptive and innate immune cells, including CD4 + and CD8 + T-cells [34, 35], dendritic cells [36], B-lymphocytes [37, 38] and natural killer (NK) cells [39].…”
Section: 1 Introductionmentioning
confidence: 99%